Effects of a virtual platform in reading comprehension and vocabulary: An alternative to improve reading abilities in Elementary school - Thorne, Cecilia (2013)
Given, on the one hand, the poor results obtained by Peruvian children in the national and international reading assessments. And on the other hand, the increased investment intechnology for schools in the country, this study aimed to develop and test an online tool to improve reading comprehension. In order to do this, the reading comprehension strategies and vocabulary activities from the research-based digital environment ICON were adapted to design the platform LEO. A total of 88 fifth graders from urban middle-to-low-income private schools from Lima participated in this quasi-experimental study, which involved acontrol group and a treatment group that participated in a 12-week teacher-mediated digital intervention. All participants were administered reading and vocabulary assessments pre and post intervention. Results revealed that students who participated in the intervention achieved higher comprehension scores for narrative texts and higher vocabulary scores than those of the control group.